2006
DOI: 10.1016/j.ssc.2006.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Slow dynamics, aging, and glassy rheology in soft and living matter

Abstract: We explore the origins of slow dynamics, aging and glassy rheology in soft and living matter. Non-diffusive slow dynamics and aging in materials characterised by crowding of the constituents can be explained in terms of structural rearrangement or remodelling events that occur within the jammed state. In this context, we introduce the jamming phase diagram proposed by Liu and Nagel to understand the ergodic-nonergodic transition in these systems, and discuss recent theoretical attempts to explain the unusual, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
44
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 71 publications
5
44
0
Order By: Relevance
“…It is unlikely that such a correlation exists for events occurring in non-overlapping regions; in contrast, successive events in the same region will lead to partially correlated changes of phase when the direction of displacement persists during several events. Thus, p = 1.65 indicates intermittent supradiffusive motion, a behaviour close to the ballistic motion reported for many jammed systems 19,20 . Figure 3b shows the 1/σ 2 φ -dependence of χ * .…”
supporting
confidence: 76%
See 1 more Smart Citation
“…It is unlikely that such a correlation exists for events occurring in non-overlapping regions; in contrast, successive events in the same region will lead to partially correlated changes of phase when the direction of displacement persists during several events. Thus, p = 1.65 indicates intermittent supradiffusive motion, a behaviour close to the ballistic motion reported for many jammed systems 19,20 . Figure 3b shows the 1/σ 2 φ -dependence of χ * .…”
supporting
confidence: 76%
“…Surprisingly, as ϕ increases β grows above one, finally saturating around 1.3. A similar 'compressed' exponential relaxation has been observed in single 19,20 and multiple 21 scattering experiments on systems close to jamming, usually associated with ultraslow ballistic motion.…”
supporting
confidence: 69%
“…Generically, these materials are characterized by slow dynamics and often fail to achieve equilibrium within time scales that can be achieved in the laboratory [1]. They are therefore classified as soft glassy materials and serve as excellent model systems in the understanding of the non-equilibrium glass transition in hard condensed matter systems [2,3]. As a direct consequence of the particle crowding that exists in these materials, the constituent entities are arrested in a cage formed by their neighbors.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally observed that for concentrations above 1 volume %, an aqueous suspension of Laponite undergoes ergodicity breaking soon after mixing Laponite powder in water [6,7]. During the last decade, various optical tools have been employed to investigate such ergodicity breaking and the subsequent aging dynamics in this system [3]. The intensity autocorrelation function measured in dynamic light scattering (DLS) experiments is seen to exhibit a two-step decay.…”
Section: Introductionmentioning
confidence: 99%
“…The non-stationary, slowly-evolving dynamics of deeply quenched fluids, referred to as aging, has been the subject of considerable attention over the last decade [1,2]. Concentrated emulsions [3], colloidal gels [4], and aqueous clay suspensions [5] are some examples of aging systems.…”
mentioning
confidence: 99%